DEVASTATING EFFECT OF NATURAL CALAMITY ON THE PRODUCTIVITY AND INCOME OF SUGARCANE FARMERS AT EASTERN VISAYAS, PHILIPPINES: AN EXPERIENCE - Dr. Paulino A. Onal, Jr.; Dr. Violeta A. Neri; Ken A. Buayaban; Owen B. Buenafe (European Journal of Agricultural and Rural Education, 2022)
The Philippines as an archipelago is one of the most vulnerable countries in the world to natural disasters and looming climate change. Eastern Visayas, which were devastated heavily by Super Typhoon “Haiyan” last November 23, 2013, is being tagged as one highly vulnerable area to all kinds of natural calamities. One of the farm crops directly destroyed when natural calamities occurred in this area is sugarcane. However, statistics related to losses are seldom can be found. Hence, this study aims to determine the impact of natural calamities in terms of losses to sugar production and income of the farmers. The existing “Crop Damage Survey Instrument” was used in gathering data after the occurrence of every calamity. Most of the data was gathered in the 154 samples farms strategically located in the nine municipalities and one city with sugarcane crops. The data gathered were encoded in the excel format and analysis was done using the SPSS software. For the years 2017 to 2018, the year 2020 five calamities had occurred thus it was described as “often”. In the years 2017 and 2021 the area damage was large hence it was described as “very highly damaged” In terms of losses in sugar and income the year 2017 was described as “very high losses” Another or more studies should be conducted related to this subject in order to contribute on the knowledge related to this subject matter.